Immunoglobulin E-virus phenotypes of infant bronchiolitis and risk of childhood asthma - Shibata, Ryohei; Zhu, Zhaozhong; Ooka, Tadao; Freishtat, Robert J.; Mansbach, Jonathan M.; Pérez-Losada, Marcos; Ramos-Tapia, Ignacio; Teach, Stephen; Camargo, Carlos A.; Hasegawa, Kohei (Frontiers in Immunology, 2023)
Background Bronchiolitis is the leading cause of infant hospitalization in U.S. and is associated with increased risk for childhood asthma. Immunoglobulin E (IgE) not only plays major roles in antiviral immune responses and atopic predisposition, but also offers a potential therapeutic target. Objective We aimed to identify phenotypes of infant bronchiolitis by using total IgE (tIgE) and virus data, to determine their association with asthma development, and examine their biological characteristics. Methods In a multicenter prospective cohort study of 1,016 infants (age <1 year) hospitalized for bronchiolitis, we applied clustering approaches to identify phenotypes by integrating tIgE and virus (respiratory syncytial virus [RSV], rhinovirus [RV]) data at hospitalization. We examined their longitudinal association with the risk of developing asthma by age 6 years and investigated their biological characteristics by integrating the upper airway mRNA and microRNA data in a subset (n=182). Results In infants hospitalized for bronchiolitis, we identified 4 phenotypes: 1) tIgElowvirusRSV-high, 2) tIgElowvirusRSV-low/RV, 3) tIgEhighvirusRSV-high, and 4) tIgEhighvirusRSV-low/RV phenotypes. Compared to phenotype 1 infants (resembling “classic” bronchiolitis), phenotype 4 infants (tIgEhighvirusRSV-low/RV) had a significantly higher risk for developing asthma (19% vs. 43%; adjOR, 2.93; 95% CI, 1.02–8.43; P=.046). Phenotypes 3 and 4 (tIgEhigh) had depleted type I interferon and enriched antigen presentation pathways; phenotype 4 also had depleted airway epithelium structure pathways. Conclusions In this multicenter cohort, tIgE-virus clustering identified distinct phenotypes of infant bronchiolitis with differential risks of asthma development and unique biological characteristics.